The origin and formation of Sichuan opera - Wu, Yating; Abdul Rahman, Ahmad Rizal; Perumal, Velu; Siow, May Ling (Scientific Bulgarian Communications, 2021)
Sichuan opera mainly survives in the actual aesthetic activities of the living subjects in Sichuan for a long time. However, since the aesthetic activity of Sichuan opera is a kind of perceptual practice with extensive social connections and full of changes, people should rationally grasp Sichuan opera as an aesthetic object. It is difficult to comprehensively and systematically clarify the difference and connection between Sichuan Opera and other types of opera. The author believesd that the origin time of Sichuan Opera is uncertain by consulting, discussing, and summarying references and books. The origin of Sichuan opera has always been controversial, in `Minor History of Sichuan Opera' written by An Min, `General History of Chinese Sichuan Opera' by Deng Yunjia, `Immigration into Sichuan and Stage Life' by Jiang Weimin, `Sichuan Opera' by Chen Zhiwei, and `Sichuan Opera' by Du Jianhua In the `Analysis of the Origin of Sichuan Opera-Also Discussing the Study of the History of Drama' written by Zhong Tao, they all mentioned the origin of Sichuan Opera, but their views are different. The complicated historical composition of Sichuan Opera, it consists of the history of Sichuan Opera's music history, performance history, drama history, stage history and so on. The author believes that the origin of Sichuan Opera cannot be determined.